“KUTADGU BILIG” AND “TEMUR TUZUKLARI” - Zohidjon Sadikov (Scholar Express Journal, 2021)
The article compares the first Turkic preaching work “Kutadgu bilig” of Yusuf Khos Hajib to Emir Timur's “Temur tuzuklari” and summarizes the common ideas, thoughts, and comments on their specific aspects.
Keywords: Ancient Turkic language; preaching work; literary unity; an encyclopedic work